Investigation of the localization phenomenon in quaternary BInGaAs/GaAs for optoelectronic applications. (March 2017) - Hidouri, Tarek; Hamila, Radhia; Fraj, Ibtissem; Saidi, Faouzi; Maaref, Hassen; Rodriguez, Philippe; Auvray, Laurent
Abstract: In this paper, single quantum well (SQW) structure of Bx Iny Ga1-x-y As/GaAs lattice-matched to GaAs has been grown by metal organic vapor phase epitaxy (MOVPE). The sample was characterized morphologically and structurally using the atomic force microscopy AFM, transmission electron microscopy TEM and high resolution X-ray diffraction HRXRD measurements. The optical study was investigated by photoluminescence (PL) spectroscopy as a function of temperature. The PL peak energy, the full width at half maximum (FWHM) and the PL intensity, versus temperature, exhibit anomalous behaviors such as S-shaped and N-shaped. They were attributed to the creation of a fluctuation potential in the band edge of the host material from the non-uniform distribution of boron atoms in the structure induced exciton localization. We investigate the localization phenomenon by excitation density variation. Then, a quasi-steady state rate-equation model for temperature dependent luminescence spectra of localized-state material system (LSE) was presented to quantitatively reinterpret the band gap emission process. The novel analytical models, compared with the classical ones, were used to fit the PL peak energy evolution. Good agreement between experimental and theoretical results has been observed using the modified Pässler model. Modeling results will be discussed based on specified parameters. These results can improve the fundamental properties of quaternary based on light-emitting and optoelectronic devices. Highlights: Structural, morphological and optical characterization of BInGaAs/GaAs SQW. Abnormal behavior of the luminescence keys. Novel and classical models were used to fit the S-shaped behavior. Based on the LSE model, the modified Pässler model was the most accurate fit of the Eg (T) temperature dependence. Qualitative and quantitative interpretations of energy band gap evolution based on the LSE model were investigated.